2013
DOI: 10.1111/all.12099
|View full text |Cite
|
Sign up to set email alerts
|

Distant lymph nodes serve as pools of Th1 cells induced by neonatal BCG vaccination for the prevention of asthma in mice

Abstract: These data demonstrate that ILN serves as a 'weapon' pool of Th1 cells following BCG vaccination, and these cells are ready for the migration into the inflamed lungs upon the allergen challenge, thereby inhibiting allergen-induced airway disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 31 publications
2
16
0
1
Order By: Relevance
“…We further demonstrated that BCG vaccination effectively attenuated chronic OVA challenge‐induced airway remodelling in mice . The mechanisms of this protective effect were most likely due to an induced Th1 response by BCG . Interestingly, these BCG‐induced Th1 cells mainly resided in draining lymph nodes and had the potential for proliferation and differentiation.…”
Section: Basic Science Researchmentioning
confidence: 72%
See 3 more Smart Citations
“…We further demonstrated that BCG vaccination effectively attenuated chronic OVA challenge‐induced airway remodelling in mice . The mechanisms of this protective effect were most likely due to an induced Th1 response by BCG . Interestingly, these BCG‐induced Th1 cells mainly resided in draining lymph nodes and had the potential for proliferation and differentiation.…”
Section: Basic Science Researchmentioning
confidence: 72%
“…Interestingly, these BCG‐induced Th1 cells mainly resided in draining lymph nodes and had the potential for proliferation and differentiation. Upon OVA challenges, these Th1 cells were able to migrate into the local airways to inhibit the allergic Th2 immune response . Studies from other groups also demonstrated the protective role of BCG in asthmatic inflammation .…”
Section: Basic Science Researchmentioning
confidence: 94%
See 2 more Smart Citations
“…BCG possesses several attributes that make it a highly favorable candidate for development as a recombinant vaccine vector. These include its ability (i) to express transgenic antigens from pathogens, such as HIV, (ii) to induce strong T-cell responses associated with the release of gamma interferon (IFN-␥) and other Th 1 cytokines, and (iii) to generate T-cell responses specific for transgenic antigens, which can ultimately be increased by heterologous boost vaccination (1)(2)(3)(4)(5)(6)(7)(8). The aforementioned responses are generated with high doses of recombinant BCG (rBCG).…”
mentioning
confidence: 99%